2022
DOI: 10.3390/economies10030057
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Intention to Use Financial Technology among Vietnamese Youth: Research in the Time of COVID-19 and Beyond

Abstract: This study focuses on understanding the factors that affect the intention of using financial technology among young Vietnamese in the context of the COVID-19 pandemic. Fintech studies are abundant in developed countries and mainly focus on consumers’ conditions, awareness, habits, and capital. These are expected to differ significantly from the situation in developing countries. We have reviewed factors that can affect the user’s intention, including the Perceived Benefit (PB), Perceived Risk (PR), Belief (B),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
9
12
2
Order By: Relevance
“…Consistent with all models based on psychological theories, which assert that individual behaviour is predictable and influenced by individual intention (Allah Pitchay et al, 2020;Khuong et al, 2022;Rahi & Abd. Ghani, 2019;Yu, 2012), the Unified Theory of Acceptance and Usage of Technology (UTAUT) and the UTAUT2 support the notion that behavioural intention has a substantial impact on technology use (Venkatesh et al, 2003(Venkatesh et al, , 2012.…”
Section: H14: Behavioural Intention (Int)supporting
confidence: 71%
See 1 more Smart Citation
“…Consistent with all models based on psychological theories, which assert that individual behaviour is predictable and influenced by individual intention (Allah Pitchay et al, 2020;Khuong et al, 2022;Rahi & Abd. Ghani, 2019;Yu, 2012), the Unified Theory of Acceptance and Usage of Technology (UTAUT) and the UTAUT2 support the notion that behavioural intention has a substantial impact on technology use (Venkatesh et al, 2003(Venkatesh et al, , 2012.…”
Section: H14: Behavioural Intention (Int)supporting
confidence: 71%
“…Amin et al (2008) discovered that an individual's behavioural intention to utilise mobile banking is influenced by their immediate surroundings, such as friends and family. Previous studies in a similar context also found that social influence significantly affects intention (Akhtar et al, 2019;Khuong et al, 2022;Mahfuz et al, 2016).…”
Section: Hypothesessupporting
confidence: 52%
“…Alshari and Lokhande (2022) analysed the influence of demographic factors on fintech services using a survey method and found that age does not have a significant effect on payment services, whereas gender, income and education have a significant impact, including on different aspects of customer behaviour. Khuong et al (2022) studied the attitudes of the Z generation (Vietnamese aged 18-24 years) towards the use of fintech technologies and found that perceived benefit and belief have the strongest influence on user intentions, although the relationship is not statistically significant enough. The two studies (Alshari & Lokhande, 2022;Khuong et al, 2022) were conducted in individual countries and may not reflect the behaviour of youth around the world; nonetheless, they point out that demographic differences and generational change are important for the development of fintech.…”
Section: Socio-demographic Differences Among Fintech Usersmentioning
confidence: 99%
“…Khuong et al (2022) studied the attitudes of the Z generation (Vietnamese aged 18-24 years) towards the use of fintech technologies and found that perceived benefit and belief have the strongest influence on user intentions, although the relationship is not statistically significant enough. The two studies (Alshari & Lokhande, 2022;Khuong et al, 2022) were conducted in individual countries and may not reflect the behaviour of youth around the world; nonetheless, they point out that demographic differences and generational change are important for the development of fintech. Every business needs to understand the behaviour of the user to increase their loyalty to the company.…”
Section: Socio-demographic Differences Among Fintech Usersmentioning
confidence: 99%
“…Financial Technology has supported financial services in many companies and countries. Financial technology has become popular since the 1990s, with strong global developments in the financial industry [2]. The accelerated growth of technology around the world also has an impact on fintech-based business strategies.…”
Section: Introductionmentioning
confidence: 99%